Prevalence and associating factors of long COVID in pediatric patients during the Delta and the Omicron variants - Tananya Lokanuwatsatien; Araya Satdhabudha; Auchara Tangsathapornpong; Pornumpa Bunjoungmanee; Phakatip Sinlapamongkolkul; Chanapai Chaiyakulsil; Paskorn Sritipsukho; Paskorn Sritipsukho; Pichaya Tantiyavarong (Frontiers Media S.A., 2023)
IntroductionThe number of pediatric COVID-19 infections is increasing; however, the data on long COVID conditions in children is still limited. Our study aimed to find the prevalence of long COVID in children during the Delta and Omicron waves, as well as associated factors.MethodsA single-center prospective cohort study was conducted. We included 802 RT-PCR-confirmed COVID-19 pediatric patients in the Delta and Omicron periods. Long COVID was defined as having symptoms for ≥3 months after infection. Parents and/or patients were interviewed by phone. Multivariable logistic regression was performed to find associated factors with long COVID.ResultsThe overall prevalence of long COVID was 30.2%. The Delta period had more prevalence than the Omicron (36.3% vs. 23.9%). Common symptoms for patients 0-3 years' old were loss of appetite, rhinorrhea, and nasal congestion. Conversely, patients 3-18 years' old had hair loss, dyspnea on exertion, rhinorrhea, and nasal congestion. However, there was no significant negative impact on daily life. Most symptoms improved after a 6-month follow-up. Factors associated with long COVID-19 conditions were infection during the Omicron period (adjusted OR: 0.54; 95% CI: 0.39-0.74, P < 0.001), fever (adjusted OR: 1.49, 95% CI: 1.01-2.20, P = 0.04) and rhinorrhea (adjusted OR: 1.47, 95% CI: 1.06-2.02, P = 0.02).ConclusionInfection during the Omicron wave has a lower prevalence of long COVID. The prognosis is often favorable, and most symptoms gradually become less. However, pediatricians may schedule appointments to surveil long COVID in children with fever or rhinorrhea as an initial symptom.